Spontaneous recanalisation of side branches occluded during percutaneous transluminal coronary angioplasty. - Shiu, M F (1985)
Percutaneous transluminal coronary angioplasty was performed in a 56 year old man with postinfarction angina. During an otherwise uncomplicated dilatation of a left anterior descending artery with a 70% stenosis two diagonal branches, each measuring 1.5 mm in diameter, were occluded. The occlusions were not associated with any adverse clinical effects, though there was a small rise in plasma creatine kinase concentration. The patient became free of angina two weeks after angioplasty, and follow up angiography showed spontaneous reappearance of the occluded side branches. Redistribution of atheromatous material and its later reabsorption may have been the mechanism for the initial occlusion and later reappearance of the vessels.